Assemblies of leaf and root mycobiomes in a temperate grassland: Dispersal limitation overpowers selection - Bai, Ren; Hu, Hang‐Wei; Ge, An‐Hui; Zhou, Meng; Sheng, Jun; Yuan, Guangyuan; Zhang, Wen‐Hao; Bai, Wenming (The Journal of ecology, 2025)
The emergence of β‐diversity of plant‐associated fungi across diverse coexisting host plant species in natural habitats is intricately linked to specific community assembly processes. Despite this, the relative contributions of various assembly processes to the observed β‐diversity patterns, as well as the influence of plant traits on these contributions, are still poorly understood. Here, we investigated the leaf/root‐associated fungal communities across nine coexisting dominant herbaceous perennials in a temperate grassland that had undergone a 17‐year mowing treatment. We elucidated the β‐diversity components and community assembly processes of these fungal communities. Furthermore, we explored relationships between leaf/root functional trait variations and fungal community assemblies. We tested the following hypotheses: (1) both species turnover and nestedness are important components of the fungal β‐diversity, with selection predominating in the fungal community assemblies; (2) mowing enhances the contributions of nestedness/selection; (3) plant trait variations significantly affect the fungal community assembly processes. Unexpectedly, our findings demonstrated a predominance of leaf/root fungal species turnover among coexisting plant hosts, contrasting with nestedness. Moreover, dispersal limitation emerged as the primary factor shaping fungal community assemblies, rather than selection processes. Although mowing significantly inhibited plant growth, its effects on the overall patterns of fungal assemblages were limited. We further observed that higher degrees of plant trait variations were primarily linked to stronger dispersal limitation, with a relatively weaker influence on heterogeneous selection. Additionally, the impact of plant traits on the selection process of root‐associated fungi was more pronounced compared to that of leaf‐associated fungi. Synthesis. Our study reveals that the β‐diversity of fungi associated with coexisting plants in natural grasslands is primarily attributed to fungal species replacement rather than gain‐and‐loss dynamics among these plants. Concurrently, this observed pattern is largely governed by dispersal limitation as opposed to selection. We propose that the primary mechanism through which plant hosts and their traits influence the structures of associated fungal communities is by limiting fungal dispersal, while niche differentiation among fungal taxa plays a secondary role. These findings offer a mechanistic insight into the assemblies of plant mycobiomes and further elucidate the plant‐mycobiome relationships within complex plant communities. In a temperate grassland, the formation of β‐diversity of leaf/root‐associated fungi among coexisting plants is primarily driven by species turnover, with nestedness having a minor role. Fungal community assembly is dominated by dispersal limitation rather than selection. Long‐term mowing disturbances do not significantly promote nestedness or selection. Plant trait variations exert only a weak influence on fungal community niche assembly.